The Effectiveness Of The Medan City Police Department's Women And Children Protection Unit Services In Handling Cases Of Violence Against Children And Women Lp / B / 2861 / Viii / 2025 / KDRT - Nazla, Dzul Hairani; Rahmayanti, Rahmayanti; Ismaidar, Ismaidar (Fakultas Hukum Dehasen, 2026)
Violence against children and women is a serious problem that requires effective legal action and services oriented toward victim protection. The role of law enforcement officials, particularly the Women and Children Protection Unit (PPA), is crucial in ensuring that case handling processes comply with legal provisions while providing a sense of security for victims. This study aims to analyze the legal procedures implemented, identify service barriers, and assess the effectiveness of the Medan Police's PPA Unit in comprehensively handling cases of violence against children and women.This study used a qualitative method with an empirical legal approach and a legislative approach. Data were obtained through observation, interviews, and a literature review of legal regulations and documents related to case handling. Data analysis was conducted descriptively to systematically describe service practices and the implementation of legal procedures in the field.The results show that case handling procedures have been implemented systematically, starting from receiving reports, examining victims and witnesses, medical examinations, victim assistance, and transferring cases to the prosecutor's office. Service barriers include internal factors related to the preparation of evidence, as well as external factors influenced by the victim's psychological condition and family relationships with the perpetrator. The Medan Police PPA Unit's services are considered quite effective through improving the quality of case handling.